Գրական արեւմտահայերէնի քերականական համակարգի տեղաշարժերը՝ ըստ արեւմտահայերէնի առկայ դասագիրքերու (բայ) - Ֆիշենկճեան, Անի (ՀՀ ԳԱԱ ԼԻ հրատարակչություն)
In literary Western Armenian, there have been shifts in the verb conjugation system. They are reflected primarily in the verb ending ուլ, verbal affixes, forms of irregular conjugation, the formation of irregular and incomplete verbs, etc. This article examines how the formation of two forms of irregular verb conjugation (with and without changing the verb base) is presented in textbooks, the various manifestations of these verbs, discusses the problems associated with changes in Western Armenian textbooks, shows how the forms of irregular verb conjugation are determined in various Western Armenian grammar textbooks. В литературном западноармянском произошли сдвиги в системе спряжения глаголов. Они отражены прежде всего в глагольном окончании ուլ, глагольных аффиксах, формах неправильного спряжения, образовании неправильных и неполных глаголов и т.д. В данной статье исследуется, как представлено образование двух форм неправильного спряжения глаголов (с изменением глагольного основания и без его изменения) в учебниках, различные проявления этих глаголов, рассматриваются проблемы, связанные с изменениями в учебниках западноармянского, показано, как определяются формы неправильного спряжения глаголов в различных учебниках грамматики западноармянского.
Keywords: Լեզվաբանություն